Pemanfaatan Jejaring Sosial Sebagai Media Pendukung Proses Pembelajaran Teknologi Informasi Dan Komunikasi di Sekolah Menengah Atas Negeri 4 Payakumbuh - Kiki Nidya Stephanie; Legiman Slamet; Ahmad Jufri (Universitas Negeri Padang, 2014)
This study specifically aims to determine the use of facebook amongst students of SMAN 4 Payakumbuh, and to investigate the students' response to the use of facebook as a medium of learning support. This study uses a descriptive study, in which only describe a situation or event does not explain the relationship and do not test hypotheses and make predictions. The study population was a tenth grade students of SMAN 4 Payakumbuh, semester 1. By using purposive sampling technique, class X4 obtained as a sample class. Data were obtained from the research literature (library research) and field research (field research) with a questionnaire instrument that contains 22 written statement, which must be answered by the respondents. A technique of data analysis in this research is to use the technique of percentage. The results showed that, in general, students of SMAN 4 Payakumbuh have regular and accustomed to using facebook, and for this use the facebook application just for fun. The research shows that the use of facebook as a medium of learning support have a positive impact for students, because not only students can play the facebook app, but can also use facebook as a medium for learning and discussion about learning. Keyword : facebook, media, descriptive